(untitled) - Lutz, Charles Gregory (Oxford, 2001)
Provides reviews of the fundamental theory and examples of practical applications for numerous aspects of genetic improvement in aquaculture.
Keywords: Aquaculture,Aquatic animals,Nuôi trồng thủy sản,Động vật ở nước; Genetics,Di truyền